Greenhouse Gas Emissions and Crop Production in West Africa: Examining the Mitigating Potential of Social Protection - Osabohien, Romanus; Matthew, Oluwatoyin; Aderounmu, Usayo; Olawande, Tomike (International Journal of Energy Economics and Policy, 2018)
This study examined how the effect of greenhouse gas (GHG) emissions on crop production can be controlled in the West Africa sub-region. Social protection was used as a mitigating factor to absorb the effect of GHG emissions. The study engaged a panel data consisting of 14 Economic Community of West African States member countries to analyse the data which was sourced from the World Development Indicators and Country Policy and Institutional Assessments for the period 2000-2016, with the use of fixed and random effects econometric model. Results showed that an increase in greenhosue gas emissions reduced crop production by 0.13%, this is through the lowering of crop yields resulting from the emissions of GHGs. Therefore, based on the findings, the study recommended that effective social protection programmes such as the Linkage Assurance Crop Insurance Solutions that will provide cover against unavoidable loss of crops or resulting directly from the insured perils such as insurance against losses incurred from GHG emissions and other crop demaging activities shoud be implemented to reduce risks associated with farming. Keywords: Greenhouse Gas Emissions, Social Protection, Crop Production, West Africa JEL Classifications: D13, Q15, R11, L98 DOI: https://doi.org/10.32479/ijeep.7056